Comparison of Patient Controlled Epidural Analgesia (PCEA) with basal infusion and Programmed Intermittent Epidural Bolus (PIEB) with PCEA in labour analgesia - A Year Retrospective Study / Zawiah Kassim ...[et al.] - Kassim, Zawiah; Mohd Nor, Norliza; Mokhtar, Ariffah; Mohamad, Suhaina; Osman, Sarina; Adnan, Isqandar (Universiti Teknologi MARA Cawangan Selangor, 2021)
Introduction: Over three decades, patient-controlled epidural analgesia with a basal infusion regimen (PCEA+BI) has successfully improved labour analgesia quality due to its advantage in allowing self-titration by the parturients. Recently, a newer programmed intermittent epidural bolus with PCEA regimen (PIEB+PCEA) was suggested to improve the epidural spread of local anaesthetic hence resulted in better analgesia quality and higher maternal satisfaction. Methods: We conducted a one-year retrospective analysis of data from obstetric analgesia service record sheet and hospital information system comparing maternal satisfaction towards their labour analgesia quality, mode of delivery and neonatal Apgar scores between these two methods of epidural delivery techniques. A total of 343 parturients were recruited in this study (PCEA+BI n=171, PIEB+PCEA n=172). Results: There were no significant difference in maternal satisfaction between the two groups (P=0.398) with a higher percentage of excellent satisfaction were found in the PIEB+PCEA group (PIEB+PCEA 146/172 (84.9%) vs PCEA+BI 138/171 (80.7%)). No significant difference in the mode of delivery (P=0.296). However, the PIEB+PCEA group shown a higher spontaneous vaginal delivery rate (PIEB+PCEA 87/172 (50.6%) vs PCEA+BI 70/171 (40.9%) and lower Caesarean delivery rate (PIEB+PCEA 71/172 (41.3%) vs PCEA+BI 87/171 (50.9%)). Despite statistically significant differences found in Apgar scores at 1 minute (P=0.036), there was no significant difference in the scores at 5 minutes (P=0.107). Mean Apgar scores (SD) at 1 minute and 5 minutes for PIEB+ PCEA were 7.77(0.85) and 8.91(0.55) respectively and for PCEA + basal infusion, the scores for 1 minute and 5 minutes were 7.92(0.39) and 8.98(0.19) respectively. Conclusion: PIEB with PCEA is a newer epidural delivery technique for labour analgesia which produces a comparable outcome to PCEA with basal infusion.